Pandangan Hidup Etnis Madura dalam Kèjhung Paparèghân - Fitri Nura Murti (Postgraduate Program Magister Pendidikan Agama Islam, 2017)
Literary works comes as a reaction of the human experience to life. Through literature, we can see the spirit and way of life of a community culture. View of life is the concept of a person or a particular social group in society that intends to respond and explain all the problems facing the people of this world. Kèjhung paparèghân is one of the classic forms of oral literature that is now quite rare. Kèjhung paparèghân form like a song or poem rhyme shaped madura rhythm typical of Madura ethnic communities. Kèjhung paparèghân hereditary preserved from generation to generation orally. That's why kèjhung paparèghân including oral folklore literature. The analysis in this study used discourse analysis with data sources show ludruk in Jember. From the analysis, kèjhung paparèghân contain moral values that reflect the views of ethnic Madurese living. The conclusions of this analysis is the view of life Madurese community can not be separated from religious values of Islam. Their adherence to Islam become an important identity for the Madurese. Madurese communities have the view that life is